Polymorphisms in the control region of mitochondrial DNA associated with elite Japanese athlete status - Mikami, E.; Fuku, N.; Takahashi, H.; Ohiwa, N.; Pitsiladis, Y. P.; Higuchi, M.; Kawahara, T.; Tanaka, M. (Scandinavian Journal of Medicine & Science in Sports, 2013)
The control region of mitochondrial DNA (mtDNA) contains the main regulatory elements for mtDNA replication and transcription. Certain polymorphisms in this region would, therefore, contribute to elite athletic performance, because mitochondrial function is one of determinants of physical performance. The present study was undertaken to examine the effect of polymorphisms in this region on elite athlete status by sequencing the mtDNA control region. Subjects comprised 185 elite Japanese athletes who had represented Japan at international competitions (i.e., 100 endurance/middle-power athletes: EMA; 85 sprint/power athletes: SPA), and 672 Japanese controls (CON). The mtDNA control region was analyzed by direct sequencing. Frequency differences of polymorphisms (minor allele frequency >/= 0.05) in the mtDNA control region between EMA, SPA, and CON were examined. EMA displayed excess of three polymorphisms [m.152T>C, m.514(CA)n repeat (n >/= 5), and poly-C stretch at m.568-573 (C >/= 7)] compared with CON. On the other hand, SPA showed greater frequency of the m.204T>C polymorphism compared with CON. In addition, none of the SPA had m.16278C>T polymorphism, whereas the frequencies of this polymorphism in CON and EMA were 8.3% and 10.0%, respectively. These findings imply that several polymorphisms detected in the control region of mtDNA may influence physical performance probably in a functional manner.